Public Value Creation by Private Sector through Cross-Sector Collaboration: A Case Study of the Gojek Wirausaha Program - Kurniawati, Iin; Kustulasari, Agustina (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2020)
Social reality that is always dynamic in practice often causes the "public" and "private" spheres to become increasingly difficult to separate. Several studies state that public value creation is no longer the exclusive domain of the government, the private sector can even carry out innovative ideas for community needs that are widely applied by the start-up industry. This research is a case study of the Gojek Wirausaha Program that intentions to help MSMEs 'upgrade' by providing business training and technology access through digital platforms. This article aims to determine how the private sector creates public value at the practical level in the context of a developing country. This study's contribution is the availability of new data in a different context from the majority of previous studies. It is expected to provide a better understanding of public value creation, mainly through cross-sector collaboration. The study uses five primary data collected through semi-structured interviews and a few secondary data by conducting literature reviews from documents, newspapers, mass media, and journal articles. The finding shows that the creation of public value in practice has its dynamics influenced by the interests of actors who, despite being private corporations, would like to create public value.